The Influence of the Motor Vehicle Tax Reduction Program and Exemption of Name Transfer Duty on Taxpayer Compliance in the City of Banjararu, South Kalimantan - Subhan, Rizky; Junaidy, Junaidy (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
Tax is a mandatory contribution that applies to every tax on tax objects and the proceeds received from the tax are handed over to the government. In essence, national development in a country is carried out by the community together with the government. The aim of this research is to determine the effect of reduced motor vehicle tax and exemption from transfer of title fees on taxpayer compliance. This research uses quantitative research based more on data that can be calculated to produce a solid quantitative assessment. With measurement using a Likert Scale. The samples in this research were 100 motor vehicle tax payers. This research questionnaire was tested using validity and reliability tests. Hypothesis testing data analysis uses multiple linear regression. Based on the results of hypothesis testing, it can be concluded that tax whitening has a positive and significant effect on taxpayer compliance. Exemption from transfer of name fees has a positive and significant effect on taxpayer compliance. And simultaneously, the variables of taxpayer whitening and exemption from transfer of name fees have a positive and significant effect on taxpayer compliance. This program can support the Banjarbaru city government to maximize revenue in the tax sector. For further research, you can use other variables in research on taxpayer compliance because in this study it only had a small effect of 41.2%, the remaining 58.8% was influenced by other variables.